Impact of no, distal, and proximal deep vein thrombosis on clinical outcomes in patients with acute pulmonary embolism: From the COMMAND VTE registry. Issue 4 (April 2021) - Nishiwaki, Shushi; Morita, Yusuke; Yamashita, Yugo; Morimoto, Takeshi; Amano, Hidewo; Takase, Toru; Hiramori, Seiichi; Kim, Kitae; Oi, Maki; Akao, Masaharu; Kobayashi, Yohei; Toyofuku, Mamoru; et al.
Highlights: We investigated the impact of concomitant deep vein thrombosis (DVT) on clinical outcomes in pulmonary embolism patients. Proximal DVT patients had higher 90-day mortality than distal and no DVT patients. The most common cause of death was cancer in proximal and distal DVT patients. Aggressive screening for active cancer may be important in proximal DVT patients. Abstract: Background: The majority of acute pulmonary embolism (PE) is caused by thrombus developed from leg veins. However, impact of concomitant deep venous thrombosis (DVT) on clinical outcomes has not been fully evaluated in patients with acute PE. Methods: The COMMAND VTE Registry is a multicenter registry enrolling consecutive 3027 patients with acute symptomatic venous thromboembolism (VTE) in Japan. The current study population consisted of 655 acute PE patients who underwent lower extremities ultrasound examination at diagnosis for the assessment of concomitant DVT status. Results: There were 424 patients with proximal DVT (64.7%), 162 patients with distal DVT (24.7%), and 69 patients with no DVT (10.5%). The cumulative 90-day incidence of all-cause death was higher in proximal DVT patients than in distal DVT and no DVT patients (7.9%, 2.5%, and 1.4%, p  = 0.01). Regarding the causes of death, the cumulative 90-day incidence of PE-related death was low, and not significantly different across the 3 groups (1.4%, 0.6%, and 1.7%, p  = 0.62). The most frequent cause of death was cancer in proximal and distal DVT patients. There were no significant differences in 90-day rates of recurrent VTE and major bleeding, regardless of the status of concomitant DVT (2.9%, 3.2%, and 2.2%, p  = 0.79, and 1.5%, 4.4%, and 4.9%, p  = 0.46, respectively). Conclusions: Acute PE with proximal DVT at diagnosis was associated with a higher risk for short-term mortality than in patients without DVT, while the risk for short-term mortality was not significantly different between distal DVT patients and patients without DVT.